2019
DOI: 10.1111/corg.12267
|View full text |Cite
|
Sign up to set email alerts
|

Private engagement by Nordic institutional investors on environmental, social, and governance risks in global companies

Abstract: Research question/issue: The paper examines private engagements related to environmental, social, and governance (ESG) incidents as a corporate governance mechanism used by Nordic institutional investors to influence MSCI World companies. The questions addressed are how an agent-led collaborative engagement is carried out, what are the characteristics of the target companies selected, and if the successful engagements can improve ESG performance compared with pre-engagement and incomplete cases. Research findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…These between-cluster effects explain most of the variance in CSP for our sample, but we also find evidence of within-cluster effects. For example, shareholder sustainability activism may explain increased CSP when good governance indicators remain mostly unchanged (Dyck et al 2019;Semenova and Hassel 2019). Such additional complexity is beyond the scope of this article, but future research may want to zoom in more closely on the relationships between nation-level, industry-level, and firm-level governance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These between-cluster effects explain most of the variance in CSP for our sample, but we also find evidence of within-cluster effects. For example, shareholder sustainability activism may explain increased CSP when good governance indicators remain mostly unchanged (Dyck et al 2019;Semenova and Hassel 2019). Such additional complexity is beyond the scope of this article, but future research may want to zoom in more closely on the relationships between nation-level, industry-level, and firm-level governance.…”
Section: Discussionmentioning
confidence: 99%
“…Problematically, existing research on sustainability in the public administration and public policy literatures is fragmented (Armstrong and Kamieniecki 2019), and has mostly looked at how sustainable development initiatives can best be governed at the local or city level (Krause, Feiock, and Hawkins 2016;Feiock, Krause, and Hawkins 2017;Kerret and Menahem 2016). In contrast, sustainability research in the (international) business literature focuses mainly on either the effects of corporate sustainability on financial returns, or the impact of shareholder engagement on corporate sustainability (Semenova and Hassel 2019;Dyck et al 2019). As such, this literature largely ignores the role of nation-level institutions and governance (Ioannou and Serafeim 2012;Liang and Renneboog 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The name of the institutional investor or investor coalition whose private engagements were analysed is often kept anonymous. Examples of such studies include Semenova and Hassel (2019) in Norway, Dimson et al (2015) in the USA and Barko et al (2017) in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…The international scope of corporate governance research is indicated by the diverse set of governance environments studied in recent CGIR articles that include Australia, Canada, China, Germany, India, Indonesia, Iran, Italy, Japan, Korea, Russia, Spain, Sweden, Taiwan, the United Kingdom, the United States, and Vietnam, as well as multicountry studies (e.g., Deloof, Du, & Vanacker, 2020; Desender, LópezPuertas‐Lamy, Pattitoni, & Petracci, 2020; García‐Sánchez & García‐Meca, 2018; Lazzarini & Musacchio, 2018; Qian, Cao, & Cao, 2018; Tribó, 2019; Zhou & Guillén, 2019). Corporate governance research is by no means restricted to the average publicly held corporation but also deals with the unique challenges associated with specific types of firms like, for instance, audit firms (La Rosa, Caserio, & Bernini, 2019), banks (Sheedy & Griffin, 2018), business groups (Shin, Hyun, Oh, & Yang, 2018), closely held firms (Russino, Picone, & Dagnino, 2019), declining firms (Abebe & Tangpong, 2018), entrepreneurial ventures (Pérez‐Calero, Larrañeta, & Wright, 2019), family firms (Yeh & Liao, 2019), foundations (Thomsen, Poulsen, Børsting, & Kuhn, 2018), institutional investors (Semenova & Hassel, 2019), intergovernmental organizations (Federo & Saz‐Carranza, 2018), initial public offerings (IPOs) (González, Guzmán, Tellez‐Falla, & Trujillo, 2019), as well as state‐owned enterprises (Apriliyanti & Randøy, 2019). This research intensity demonstrates the spread of corporate governance studies in multiple disciplines but also leads to higher levels of fragmentation of the field.…”
Section: Introductionmentioning
confidence: 99%
“…. Corporate governance research is by no means restricted to the average publicly held corporation but also deals with the unique challenges associated with specific types of firms like, for instance, audit firms (La Rosa, Caserio, & Bernini, 2019), banks (Sheedy & Griffin, 2018), business groups (Shin, Hyun, Oh, & Yang, 2018), closely held firms (Russino, Picone, & Dagnino, 2019), declining firms (Abebe & Tangpong, 2018), entrepreneurial ventures (Pérez-Calero, Larrañeta, & Wright, 2019), family firms (Yeh & Liao, 2019), foundations (Thomsen, Poulsen, Børsting, & Kuhn, 2018), institutional investors (Semenova & Hassel, 2019), intergovernmental organizations (Federo & Saz-Carranza, 2018), initial public offerings (IPOs) (González, Guzmán, Tellez-Falla, & Trujillo, 2019), as well as state-owned enterprises (Apriliyanti & Randøy, 2019). This research intensity demonstrates the spread of corporate governance studies in multiple disciplines but also leads to higher levels of fragmentation of the field.…”
mentioning
confidence: 99%